Analisis Jurnal “Model Pengendalian Strategi, Inovasi Dan Kewirausahaan Dalam Organisasi Perspektif Ekonomi Islam” Implementasi Terhadap Lembaga Dakwah - Lalu Muh Reza Pratama; Cecep Castrawijaya (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
This study analyzes the relationship between strategic control, innovation, and entrepreneurship in organizations based on an Islamic economic perspective, with a focus on its implementation in da'wah institutions. Using a qualitative method with a library research approach, this study collected secondary data from relevant literature such as current books and journals. The results show that strategic control in Islamic economics is not only based on managerial procedures, but also sharia values such as tawhid, amanah, and maqashid sharia. Islamic innovation emphasizes the principles of maslahah, blessings, and creativity in accordance with Islamic teachings, while Islamic entrepreneurship integrates a balance between profit, social benefits, and the application of Islamic business ethics. This integration between strategic control, innovation, and entrepreneurship creates an Islamic business ecosystem that is sustainable, provides benefits to society, and is able to compete globally. This research contributes to providing insights into Islamic values-based managerial models that are relevant to contemporary challenges, including digitalization and sustainability.